Individual, situational, and cultural correlates of acquiescent responding: Towards a unified conceptual framework. (9th March 2019) - Lechner, Clemens M.; Partsch, Melanie V.; Danner, Daniel; Rammstedt, Beatrice
Abstract : Acquiescence ('yea‐saying') can seriously harm the validity of self‐report questionnaire data. Towards a better understanding of why some individuals and groups acquiesce more strongly than others do, we developed a unified conceptual framework of acquiescent responding. Our framework posits that acquiescent responding is a joint function of respondent characteristics (e.g. age, education, values), situational/survey characteristics (e.g., interview privacy, respondents' interest), and cultural characteristics (e.g., social norms, economic development). The framework posits two putative mechanisms through which these characteristics may relate to acquiescence: cognitive processing capacities and deferential communication styles. Multilevel analyses using data from 60 heterogeneous countries from the World Values Survey ( N = 90, 347) support our framework's proposition that acquiescence is a joint function of respondent, situational, and cultural characteristics. Acquiescence was higher among respondents who were older (over 55 years old), less educated, who valued deference (i.e., conformity and tradition), and, unexpectedly, were male. Interview privacy corresponded to lower acquiescence, but this association was small and vanished after including respondent characteristics. Unexpectedly, acquiescence was higher in interviewees who showed a stronger interest in the interview. Finally, acquiescence was considerably higher in countries with stronger social norms of deference. We discuss implications of these findings for the validity of research based on self‐report data and delineate how our framework can guide future inquiries into acquiescent responding.